Case studies on the use of temperature-dependent susceptibility for the characterisation of magneto-mineralogical changes during metamorphism - Kontny, Agnes; Wall, Helga de (Physics and chemistry of the earth. Part A, Solid earth and geodesy, 2000)
Based on three case studies we show that low-, and high-temperature measurements of magnetic susceptibility (κ(T)-curves) in combination with other mineralogical and rock magnetic methods constitute a sensitive tool for the identification of magnetic minerals. In this study, changes in mineral composition and grain texture, related to various metamorphic processes, are shown for minerals from the titanomagnetite and ilmenite-hematite series. If magnetite is associated with titanomagnetite, the shape of the κ(T)-curve at low temperature is significantly different from that of pure magnetite and pure titanomagnetite and we suspect that susceptibility measurements, especially low temperature, are sensitive to magnetic textures and superimposing effects due to different magnetic phases.